2022
DOI: 10.1186/s12876-022-02263-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum uric acid to HDL-cholesterol ratio is associated with onset of non-alcoholic fatty liver disease in a non-obese Chinese population with normal blood lipid levels

Abstract: Background Recent studies have demonstrated the presence of associations between metabolic syndrome and the onset of nonalcoholic fatty liver disease (NAFLD). Metabolic syndrome, in turn, has been found to be linked to high serum uric acid to HDL-cholesterol ratios (UHR). However, the relationship between UHR values and the occurrence of NAFLD in non-obese individuals remains unknown. The present study aimed to examine the possible correlation between UHR values and NAFLD onset among a non-obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…As indicated, high SUA levels are related to more than twice the levels of alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase. 6,26,27 The results of the present study indicate that as SUA increased by 1 μmol/L, the influence of developing liver diseases increased by 1.003 times, which is consistent with previous studies. Overall, the results of this study further support the significance of SUA levels in standard treatment for gout.…”
Section: Discussionsupporting
confidence: 92%
“…As indicated, high SUA levels are related to more than twice the levels of alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase. 6,26,27 The results of the present study indicate that as SUA increased by 1 μmol/L, the influence of developing liver diseases increased by 1.003 times, which is consistent with previous studies. Overall, the results of this study further support the significance of SUA levels in standard treatment for gout.…”
Section: Discussionsupporting
confidence: 92%
“…Model2 Model3 ALT, alanine aminotransferase; AST, aspartate aminotransferase; GGT, gamma-glutamyl transferase; ALP, alkaline phosphatase; Scr, serum creatinine; FBG, fasting blood-glucose; HbA1c, glycosylated hemoglobin; FINS, fasting insulin; TG/HDL-C, triglycerides to high-density lipoprotein-cholesterol ratio; TC/HDL-C, cholesterol to HDL-C ratio; FFA/HDL-C, free fatty acid to HDL-C ratio; UA/HDL-C, uric acid to HDL-C ratio; LDL-C/HDL-C, low-density lipoprotein-cholesterol to HDL-C ratio; APOB/A1, apolipoprotein B to apolipoprotein A1 ratio. Previous studies on the correlation between lipid-lipoprotein ratios and NAFLD have been reported (9,11,16,17,23). Ren et al (11) concluded that the TC/HDL-C ratio had a significant predictive value for NAFLD, and ROC analysis showed that the AUC (0.645) was greater than other serum lipids.…”
Section: Model1mentioning
confidence: 98%
“…Ren et al (11) concluded that the TC/HDL-C ratio had a significant predictive value for NAFLD, and ROC analysis showed that the AUC (0.645) was greater than other serum lipids. In addition, Zhu et al (9) suggested that the predictive value of UA/HDL-C was significantly higher than LDL-C/HDL-C, non-HDL-C/HDL-C and ALT/AST in a non-obese population, even when UA and LDL-C levels were within the normal range. In a 5-year longitudinal cohort study of 9767 non-obese subjects with normal lipids, Cox proportional hazard regression model confirmed that high LDL-C/HDL-C ratios significantly increased the risk of NAFLD in non-obese Chinese subjects with normal lipids (16).…”
Section: Model1mentioning
confidence: 99%
See 2 more Smart Citations